Rural Sport Tourism Development and Governance: Evidence from Jurangmangu Adventure Village - Elang Purbha Sejati; Paphada Suebplai; Mario Ramil Pepito (Multidisciplinary Journal of Tourism, Hospitality, Sport and Physical Education, 2026)
Purpose of the study: This study aims to explore the current sport tourism potential and development challenges of Jurangmangu Adventure Village in Pemalang, Indonesia, and to derive cross-national comparative insights by examining analogous rural sport tourism governance experiences in Thailand and the Philippines. Methodology: This study employed a qualitative descriptive approach within an interpretivist framework. Data were collected from March to August 2025 through structured interviews with purposively selected informants, complemented by observation and document analysis. Thematic analysis and triangulation ensured credibility. Findings are presented as an in-depth descriptive case study due to the limited but information-rich informant base. Main Findings: Jurangmangu Adventure Village demonstrates strong sport tourism potential through Mount Slamet trekking, downhill mountain biking, agritourism, educational tourism, and community-based hospitality. However, development challenges remain in institutional governance, funding dependency, and digital promotion. The integrated family sport tourism model combining adventure activities and educational experiences represents a distinctive and scalable approach aligned with rural tourism practices in Southeast Asia. Novelty/Originality of this study: This study offers the first qualitative examination of Jurangmangu Adventure Village as an integrated rural sport tourism destination within a Southeast Asian comparative framework. By connecting Indonesian field evidence with Thailand and Philippine governance perspectives, the study provides new insights into community-based sport tourism development, highlighting transferable strategies for strengthening rural destination management and sustainability.